Product Management Model for Entrepreneurship - Mascaro Sifuentes, Jose (2023)
After the COVID pandemic in 2019, the number of startups and entrepreneurship ventures grew exponentially. This article aims to develop a Product Management Model for Entrepreneurship, which allows users to have a better view of the company's financial status. The goal is to facilitate decision-making and optimal resource management. This research consists of several stages. In the first stage, an analysis of the environment and the current situation of the problem was conducted, along with a review of related research papers. Additionally, an analysis of the most important Product Management models currently in use was performed to understand the most relevant aspects and implement an innovative model. Following the study process, the foundational elements of the model were designed, including the metrics involved, as well as the relationships and connections between them, the projection time, and the financial values for simulating the model in a real-world scenario. Finally, the model will be validated by experts in the field through virtual interviews and a Likert scale-based survey. The quantitative data collected will support the validity of the model. © 2023 CISCI 2023 - Vigesima Segunda Conferencia Iberoamericana en Sistemas, Cibernetica e Informatica, Vigesimo Simposium Iberoamericano en Educacion, Cibernetica e Informatica, SIECI 2023 - Memorias.